Kesenjangan antara Kesadaran dan Perilaku Konsumsi Makanan Bersertifikat Halal pada Siswi SMAIT Mutiara Islam Cileungsi - Fristyarini, Annisa (JES (Jurnal Ekonomi Syariah), 2025)
Halal food consumption is a key aspect of Islamic practice, reflecting adherence to religious principles and concern for physical and spiritual well-being. In Indonesia, with its large Muslim population, awareness of halal products is expected to translate into consistent consumption behavior. However, a gap between awareness and actual behavior may exist, particularly among young consumers. This study investigates the gap between awareness and behavior in consuming halal food among 23 female students at SMAIT Mutiara Islam Cileungsi. Employing a descriptive quantitative approach, data were collected through online questionnaires during the 2024/2025 academic year. The findings show that students demonstrate high awareness of halal concepts, including halal certification and the principle of halalan thayyiban. Despite this awareness, their actual consumption behavior is not always consistent. The study concludes that a significant gap exists between awareness and behavior in halal food consumption among the students.